El contador Rodrigo de Albornoz y su misión financiera durante las campañas imperiales de 1535 y 1536 - Sardone, Sergio (El Colegio de México, A.C., 2022)
This article focuses on the role played by Rodrigo de Albornoz, a New Spanish accountant, during a very critical period for the Spanish Crown due to the repeated wars of Emperor Charles V against the King of France and Suleiman the Magnificent. In 1534, Albornoz returned to Castille to participate in the Tunisian campaign against the Berber corsair Hayreddin Barbarrosa, an ally of the Ottoman sultan, and the subsequent campaigns in Piedmont and Provence against the army of Frances I. In 1536, the New Spanish accountant was given the task of transporting from Seville to Italy the first gold and silver coins from the new Sevillan mint, which were used to finance the imperial army in its military campaigns.